Kampung Wisata Gurameh Sebagai Model Pemberdayaan Budidaya Ikan Tawar di Kergan Tirtomulyo Bantul - Afri Nur Cahya, Muhammad; Ash-Shiddiqy, Muhammad (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2018)
This article aims to examine the initial ideas for the formation of the Pokdakan (working group for freshwater fish farming) Mina Mulya, the stages of empowerment, and the implications of the empowerment model. These three studies are based on the problem of the consumption of freshwater fish in the Bantul community, which is increasing every year. Meanwhile, the production of fish cultivation managed by the community is very minimal. During this time the local government to meet the consumption needs of fish for households, food stalls, restaurants, until processed fish sold at tourist recreation centers taken from the area of Central Java and East Java. Seeing a potential area to develop fish cultivation production is very relevant. The intelligence of the Kergan Village community in Tirtomulyo looking at the direction of economic development based on community participation is so contextual. Through qualitative research with a case study approach, this paper found a novelty about the model of community empowerment. The model offered by the people is the “Gurameh” tourist village. As a model for empowering freshwater fish farming, Kergan Village is transformed into a more innovative and creative locus of community activities. In another aspect, the initial idea of the establishment of a “Gurameh” tourist village was initiated by Sunarto who had anxiety about the potential of his residence. Starting from comparative studies to other places, the idea of a tourist village “Gurameh” has become a model of empowerment based on fish farming. As a model, the tourist village “Gurameh” also processes the harvested fish for snacks and “souvenir” for anyone who wants to visit. Many creative and innovative activities in Kergan Village to develop in other locations. Starting from Sunarto’s idea, the concept of the trickle-down effect has spread in almost every community working group that is able to develop freshwater fish farming.Artikel ini hendak mengkaji tentang ide awal pembentukan Pokdakan Mina Mulya, tahapan pemberdayaan, dan implikasi model pemberdayaan. Tiga kajian ini dilandaskan pada masalah konsumsi ikan tawar masyarakat Bantul yang setiap tahun semakin meningkat. Sementara itu, produksi budidaya ikan yang dikelola masyarakat sangat minim. Selama ini pemerintah lokal untuk memenuhi kebutuhan konsumsi ikan bagi rumah tangga, warung makan, restoran, hingga olahan ikan yang dijajakan pada pusat rekreasi wisata diambil dari daerah Jawa Tengah dan Jawa Timur. Melihat kawasan yang cukup potensial untuk mengembangkan produksi budidaya ikan menjadi sangat relevan. Kecerdasan masyarakat Dusun Kergan Desa Tirtomulyo membaca arah pengembangan ekonomi berbasis partisipasi masyarakat begitu kontekstual. Melalui penelitian kualitatif dengan pendekatan studi kasus, paper ini menemukan kebaruan tentang model pemberdayaan masyarakat. Model yang ditawarkan oleh masyarakat adalah kampung wisata “Gurameh”. Sebagai model pemberdayaan budidaya ikan tawar, Dusun Kergan disulap menjadi lokus kegiatan masyarakat yang lebih inovatif dan kreatif. Pada aspek lain, ide awal dibentuknya kampung wisata “Gurameh” diinisasi oleh Sunarto yang memiliki kegelisahan tentang potensi tempat tinggalnya. Berawal dari studi banding ke daerah lain, ide kampung wisata “Gurameh” telah menjadi model pemberdayaan berbasis budidaya ikan. Sebagai model, kampung wisata “Gurameh” juga mengolah ikan hasil panen untuk dijadikan camilan dan ‘buah tangan’ bagi siapa saja yang hendak berkunjung. Banyak aktivitas kreatif dan inovatif di Dusun Kergan untuk terus berkembang di lokasi lain. Berawal dari ide Sunarto, konsep trickle down effect, telah menjalar hampir di setiap kelompok kerja masyarakat yang mampu mengembangkan budidaya ikan tawar.